Association of inflammatory markers with the severity of COVID-19: A meta-analysis - Zeng, Furong; Huang, Yuzhao; Guo, Ying; Yin, Mingzhu; Chen, Xiang; Xiao, Liang; Deng, Guangtong (International journal of infectious diseases, 2020)
•Monitoring the severity of COVID-19 is imperative to reduce the poor outcome.•An overview of the association of inflammatory markers with severity of COVID-19.•CRP, PCT, IL-6, ESR, SAA, and serum ferritin are indicators for severity of COVID-19.•Measurement of inflammatory markers assists to monitor the severity of COVID-19. Studies reported associations of inflammatory markers with the severity of COVID-19, but conclusions were inconsistent. We aimed to provide an overview of the association of inflammatory markers with the severity of COVID-19. We searched PubMed, Embase, Cochrane Library, Wanfang and China National Knowledge Infrastructure (CNKI) database until March 20, 2020. Weighted mean difference (WMD) and 95% confidence intervals (CIs) were pooled using random or fixed-effects models. A total of 16 studies comprising 3962 patients with COVID-19 were included in our analysis. Random-effect results demonstrated that patients with COVID-19 in the nonsevere group had lower levels for CRP (WMD = −41.78 mg/l, 95% CI = [−52.43, −31.13], P < 0.001), PCT (WMD = −0.13 ng/ml, 95% CI = [−0.20, −0.05], P < 0.001), IL-6 (WMD = −21.32 ng/l, 95% CI = [−28.34, −14.31], P < 0.001), ESR (WMD = −8 mm/h, 95% CI = [−14, −2], P = 0.005), SAA (WMD = −43.35 μg/ml, 95% CI = [−80.85, −5.85], P = 0.020) and serum ferritin (WMD = −398.80 mg/l, 95% CI = [−625.89, −171.71], P < 0.001), compared with those in the severe group. Moreover, survivors had a lower level of IL-6 than non-survivors (WMD = −4.80 ng/ml, 95% CI = [−5.87, −3.73], P < 0.001). These results were consistent through sensitivity analysis and publication bias assessment. The meta-analysis highlights the association of inflammatory markers with the severity of COVID-19. Measurement of inflammatory markers might assist clinicians to monitor and evaluate the severity and prognosis of COVID-19.